Використання водоростей для одержання енергоносіїв (утилізація СО₂) - Голуб, Н. Б.; Воєвода, Д. В. (НТУ "ХПІ", 2012)
Показана возможность использования неочищенных газовых выбросов производств для культивирования микроводоросли Chlorella vulgaris с целью получения биодизельного топлива. При периодичном режиме барбатирования культуральной среды воздухом, в котором содержание СО₂ составляет 10–15 %, увеличивается как прирост биомассы, так и липидной фракции с преобладанием высших жирных кислот С:16, С:18, что влияет на качество биодизельного топлива.

It is shown the opportunity of usage untreated gas emissions from manufacturing for cultivation microalgae Chlorella vulgaris for the future biodiesel production. It was found that the periodic aeration of culture medium with the concentration of СО₂ in air flow of about 10–15 % increased not only the biomass productivity, but also lipid content with the predominance of higher fatty acids C:16, C:18 that affects the quality of biodiesel.
The usage of algae for production fuels (utilization of СО₂)
Keywords: біодизельне паливо; альтернативні енергоносії; водорості; утилізація відходів